2014
DOI: 10.1021/jf503851z
|View full text |Cite
|
Sign up to set email alerts
|

Binding Difference of Fipronil with GABAARs in Fruitfly and Zebrafish: Insights from Homology Modeling, Docking, and Molecular Dynamics Simulation Studies

Abstract: Fipronil, which targets GABAA receptors (GABAARs), is the first phenylpyrazole insecticide widely used in crop protection and public hygiene. However, its high toxicity on fishes greatly limited its applications. In the present study, a series of computational methods including homology modeling, docking, and molecular dynamics simulation studies were integrated to explore the binding difference of fipronil with GABAARs from fruitfly and zebrafish systems. It was found that, in the zebrafish system, the H-bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 56 publications
7
44
0
Order By: Relevance
“…As depicted in Figure 6, similar binding poses of fipronil were observed in all three RDLR models, except A2′S RDLR; fipronil was erected in channel surrounded by five TM2 helices. When docked to the wild type (WT) RDLR model, the trifluoromethyl group of fipronil was oriented toward the intracellular domain, which is consistent with previous findings [26]. Interestingly, the conformation of fipronil was reversed, while 2′Ala was replaced by Ser; however, the conformation restored the same orientation as that in the WT RDLR model, while A2′S was accompanied with R0′Q.…”
Section: Resultssupporting
confidence: 88%
“…As depicted in Figure 6, similar binding poses of fipronil were observed in all three RDLR models, except A2′S RDLR; fipronil was erected in channel surrounded by five TM2 helices. When docked to the wild type (WT) RDLR model, the trifluoromethyl group of fipronil was oriented toward the intracellular domain, which is consistent with previous findings [26]. Interestingly, the conformation of fipronil was reversed, while 2′Ala was replaced by Ser; however, the conformation restored the same orientation as that in the WT RDLR model, while A2′S was accompanied with R0′Q.…”
Section: Resultssupporting
confidence: 88%
“…Each subunit in the pentameric receptor is a single polypeptide chain containing four α-helical transmembrane domains (TM1-TM4) with the second TM domain (TM2) from each subunit lining the ion-channel pore. There is evidence that several noncompetitive antagonists, such as fipronil, bind in the GABA receptor transmembrane pore domain and interact with amino acids located on TM231516. The first insect GABA-gated ion channel to be characterized in detail was RDL17, originally identified in Drosophila as being encoded by a gene associated with resistance to the insecticide dieldrin ( rdl ) ‘resistance to dieldrin’1819.…”
mentioning
confidence: 99%
“…(2019), who found that introducing the A2′S mutation into Px RDL1 of susceptible P. xylostella only caused an approximately 3‐fold increase in fipronil resistance. Molecular docking analyses demonstrated that the 6′ amino acid residue is critical for the combination of insect RDL receptors and insecticides, such as fipronil, ethiprole, and dieldrin (Zheng et al ., 2014; Sheng et al ., 2019). The T6′L mutation in Rhipicephalus microplus RDL was detected in fipronil‐ and dieldrin‐resistant strains (Hope et al ., 2010; Janer et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%